2002
DOI: 10.1191/1352458502ms779oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a short-term exercise training program on aerobic fitness, fatigue, health perception and activity level of subjects with multiple sclerosis

Abstract: Multiple sclerosis (MS) patients of an inpatient rehabilitation program have been randomly assigned to an exercise training (MS-ET) or nontraining group (MS-NI). Before and after 4 weeks of aerobic exercise training, a graded maximal exercise test with measurement of gas exchange and a lung function test was administered to all 26 patients fulfilling the inclusion criteria. Activity level, fatigue and health perception were measured by means of questionnaires. Twenty-six healthy persons served as control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
282
2
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(315 citation statements)
references
References 40 publications
22
282
2
9
Order By: Relevance
“…In addition, patients with MS have lower QOL scores and lower levels of physical activity than other persons with chronic conditions [3,[9][10]. Low QOL scores translate to lower physical activity levels, while increases in structured exercise participation and increases in physical activity levels have been shown to increase QOL scores [11][12][13]. Thus, the improvement in reported QOL in patients with MS in the present study is likely the result of the structured elliptical exercise program.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In addition, patients with MS have lower QOL scores and lower levels of physical activity than other persons with chronic conditions [3,[9][10]. Low QOL scores translate to lower physical activity levels, while increases in structured exercise participation and increases in physical activity levels have been shown to increase QOL scores [11][12][13]. Thus, the improvement in reported QOL in patients with MS in the present study is likely the result of the structured elliptical exercise program.…”
Section: Discussionmentioning
confidence: 75%
“…In general, the level of physical activity is greatly reduced in patients with MS because of multifactor causes including axonal fatigue, deconditioning, ongoing disability, and medical recommendations for limited activity [15]. Previous studies have also shown an improvement in QOL parameters related to regular physical activity in individuals with MS [11][12][13]. Increasing the overall physical activity level of patients with MS is also crucial to maintaining long-term health in the population despite the inherent challenges to patients with MS in sustaining an increased activity level [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 However, recent research indicates that people with MS who engage in exercise programs show benefits in both physical 4 and psychological 5 health, resulting in improved quality of life (QOL). [6][7][8][9] Specifically, studies have found improvement in cardiorespiratory fitness [10][11][12] and muscle strength. 13,14 In several of these studies, 4,5,10,12,14 the exercise protocol was performed by the participant in a testing environment that included supervision by an exercise specialist but no opportunity for social interaction with other study participants.…”
mentioning
confidence: 99%